O capital social sob a ótica de garantia aos credores: controvérsias, ineficiência e reflexões sobre a crise do instituto - Gabriel Siqueira Eliazar de Carvalho (2020)
Legal capital is a structural element of Brazilian corporate law. The efficiency of its legal regime, however, is questionable. The aim of the present work is to investigate exactly this perspective. For this purpose, an analysis of the history, meanings, and functions of legal capital is carried out. A critical examination of these aspects revealed that the functions of legal capital are sometimes inefficient and expendable, sometimes replaceable. As it is the most prominent function, the perspective of guaranteeing creditors was investigated in more detail. Therefore, the present work focused on the principles of truth, congruence, and intangibility, while also addressing, comparatively, other mechanisms for protecting creditors. After considering several controversies about the institute, it appears that the legal capital is not suitable to serve as a guarantee instrument. Although part of the doctrine agrees with this view, there has been no progress in investigating what the next step is within the context of this observation. We then sought to understand how the subject is treated in the respective legal regimes by analyzing American and European doctrine. After, resuming the analysis from the point of view of Brazilian law, between improving or abolishing the legal capital regime, it was concluded that the second option may be more suitable. Finally, some reflections were proposed in this regard considering a legal regime without legal capital.